THE INFLUENCE OF THE INTERNAL CONTROL SYSTEM AND ORGANIZATIONAL COMMITMENT ON FRAUD OF FINANCIAL REPORTS IN THE PUBLIC SECTOR - Ika Nirmalasari; Rida Perwita Sari (Yayasan Education and Social Center, 2023)
This study investigates the impact of internal control systems and organizational commitment on public sector financial statement fraud. This study uses a quantitative approach. The sample was the Government Internal Supervisory Apparatus (APIP) at the Inspectorate of East Java Province. This investigation utilized primary data through a questionnaire distributed to 49 participants. The analysis technique used outer and inner model tests with hypothesis testing using the WarpPLS version 7.0 statistical tool. The results showed that the internal control system had an effect on fraudulent financial reporting, and organizational commitment had an effect on fraudulent financial reporting.